Prevalence of pectinate ligament dysplasia and associations with age, sex and intraocular pressure in the Basset hound, Flatcoated retriever and Dandie Dinmont terrier. Issue 1 (December 2016) - Oliver, James; Ekiri, Abel; Mellersh, Cathryn
Abstract Background The aims of this study were to: determine the prevalence of pectinate ligament dysplasia (PLD) in populations of Basset hounds (BH), Flatcoated retrievers (FCR) and Dandie Dinmont terriers (DDT) resident in the UK; investigate possible associations between the degree of PLD and age, sex and intraocular pressure (IOP) and; investigate possible associations between IOP and age and sex. Gonioscopy was performed in both eyes of 198 BH, 170 FCR and 95 DDT and the percentage of iridocorneal angle affected by PLD was estimated and classified as unaffected (0 %), mildly affected (<20 %), moderately affected (20–90 %) or severely affected (>90 %). Rebound tonometry was performed bilaterally in the majority of enrolled dogs. Results Seventy-six of 198 (38.4 %) BH, 36/170 (21.2 %) FCR and 21/95 (22.1 %) DDT were moderately or severely affected by PLD. The prevalence of PLD was significantly higher in BH than both FCR and DDT. In all breeds there was a significant positive correlation between PLD and age. In the BH only there was a significant association between PLD and sex. In the DDT only there was a weak negative correlation between PLD and IOP and a moderately strong negative correlation between IOP and age. Conclusions PLD is prevalent and significantly associated with age in all three breeds we investigated. The linear relationship between PLD and age can be explained by the progression of PLD over time which would contribute to the high prevalence of PLD despite widespread screening.